Love in the time of cholera - Garcia Marquez, Gabriel, 1928- (New York: Penguin Books, 1989)
A love story that ranges from the late nineteenth century to the early decades of the twentieth, tracing the lives of three people and their entwined fates.
Originally published: New York : Knopf, 1988.
Translation of: El amor en los tiempos del colera.
Booklist.
Publisher's Weekly.
Wilson's Senior High School.
Adult
Keywords: Man-woman relationships -- Fiction; Love stories; Man-woman relationship -- Fiction; Colombia -- Fiction; Colombia -- Fiction; Love stories